STUDY ON THE MODIFICATION OF A HOUSEHOLD OVEN WITH COAL BRIQUETTE STOVE AS HEAT SOURCE (CILEMBU SWEET POTATO BAKING CASE STUDY) - Saukat, Muhammad
Cilembu sweet potato is usually baked with household oven heated with kerosene stove. Recent increase of kerosene price brings about a better bargaining position of coal as fuel for household purpose. This is inline with National Energy Policy to shift the fuel from kerosene to mineral coal. The usage briquette coal needs modification of oven due to the fact that flue gas from burning coal has hazardous effects on human health. The modification consist of closing flue gas hole to baking chamber, attaching fins to the inner side of the baking chambers and adding exhaust channel. The heated gas and flue gas from the stove are delivered to the left, right and back side of the baking chamber, and then will go out from the oven through the exhaust channel located at the upper side of the oven. Numerical simulation results showed that current household oven has higher temperature and better heat distribution in baking chamber than that of a modified one. Nevertheless, temperatures at the modified oven were around 337,5- 637,5 oC and suitable for sweet potato baking. Experiments on empty oven with 1,8 kg of coal indicated that baking chamber of modified oven could reach a temperature of 365 oC. Similar condition on household oven with kerosene stove showed a temperature of 205,2 oC. Another experiment using 1.0 kg of coal resulted in maximum temperature of 281,8 oC where the temperature above 180 oC last for 44 minutes with average value of 241,5oC. Further experiments were conducted to bake sweet potatoes of 2 kg with 1,4 kg, 1,2 kg and 1,0 kg of coals. Baking with 1,4 kg of coal result ed in overcooking, while that of 1,2 kg of coal produced well cooked sweet potatoes. Moreover, baking with 1,0 kg of coal resulted in uneven cooked potatoes. In case of aroma, baking with 1,2 kg of coal had better result than that of 1,0 kg. Calculation on production cost revealed that if the price of kerosene did not subsidized, the cost of using modified oven with coal stove would be comparable to that of household oven with kerosene stove. Bearing that in mind, it is necessary to carry out further modification on coal feeding system such that coal stove will be easier to use and baking can be conducted continuously.